2021
DOI: 10.3390/healthcare9111442
|View full text |Cite
|
Sign up to set email alerts
|

How Income Inequality and Race/Ethnicity Drive Obesity in U.S. Adults: 1999–2016

Abstract: Obesity is a major public health problem both globally and within the U.S. It varies by multiple factors, including but not limited to income and sex. After controlling for potential covariates, there is little evidence to determine the association between income and obesity and how obesity may be moderated by sex and family income. We examined the association between income and obesity in U.S. adults aged 20 years and older, and tested whether this relationship differs by race or ethnicity groups. For this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Using the same data set, Zare et al investigated whether the relationship between obesity and income differed by sex and race. They found that the poverty income ratio and obesity were significant and positive more often among white non-Hispanics and black non-Hispanics with middle and high income than those in the lower income category; this association was not found among Mexican Americans [ 20 ]. When considering obese women, compared to white women, Mexican American and black women faced higher income inequality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same data set, Zare et al investigated whether the relationship between obesity and income differed by sex and race. They found that the poverty income ratio and obesity were significant and positive more often among white non-Hispanics and black non-Hispanics with middle and high income than those in the lower income category; this association was not found among Mexican Americans [ 20 ]. When considering obese women, compared to white women, Mexican American and black women faced higher income inequality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the poverty income ratio and obesity were significant and positive more often among white non-Hispanics and black non-Hispanics with middle and high income than those in the lower income category; this association was not found among Mexican Americans [ 20 ]. When considering obese women, compared to white women, Mexican American and black women faced higher income inequality [ 20 ]. In looking at men, black non-Hispanic males were found to have the highest income inequality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that populations in low- and middle-income countries have a higher risk of stroke ( Saini et al, 2021 , Akinyemi et al, 2021 , Krishnamurthi et al, 2020 , Marshall et al, 2015 ). Furthermore, in addition to income disparities, racial differences also play a role in influencing disease incidence ( Zare et al, 2021 ). Some studies have shown that the risk of stroke varies by race ( Howard et al, 2019 , Finnegan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status (SES) measures a person's or family's economic and social status relative to other people or families in society. Some studies have shown that SES is associated with non-communicable diseases such as ischemic heart disease, heart failure, diabetes and obesity ( Zare et al, 2021 , Mustapha et al, 2022 , Hawkins Carranza et al, 2022 , Zare et al, 2021 ). Generally speaking, SES from higher socioeconomic status may provide direct or indirect defense against these diseases.…”
Section: Introductionmentioning
confidence: 99%